Membenahi Pergaulan Remaja Di Era Disrupsi Melalui Pendidikan Fikih - Istiqomah Nurul Azizah; Zahwa Putri Naila; Maya Wulan Sari; Soffia Soffia; Ratnatul Zaida; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2024)
This research investigates the important function of Fiqh (Islamic jurisprudence) in directing and regulating the social interactions of modern teenagers. This research is based on historical narratives in the Islamic tradition and the importance of Jurisprudence in overcoming problems such as juvenile delinquency. In addition, this research emphasizes how important it is for the principles of Fiqh to be applied practically in everyday life. According to this research, Jurisprudence education goes beyond theoretical understanding and requires the application of knowledge in the real world, which integrates theory and action. The aim of this research is to reveal methods for improving relationships in an era of disruption through the science of jurisprudence. This research uses library research methods, reviewing relevant literature to analyze the concept of adolescent social interaction from the perspective of Islamic jurisprudence. The results of this research indicate that Islamic principles are not in accordance with current teenage trends, such as changing clothing styles, increasing premarital relationships, drug propaganda, and materialistic transmission. This article emphasizes that parents and teenagers must help children bridge the gap between Islamic values ​​and modern lifestyles, with the importance of fiqh education in adolescence as a basis for living a life in accordance with Islamic values.